2018
DOI: 10.1177/0731684418816379
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the mechanical properties of aluminium metal matrix composite: A review

Abstract: In the present scenario, composites are in huge demand in the industries due to their light weight, wear resistance, stiffness and high strength. The functional and structural properties were improved according to the need of industry. Particulate reinforcement is one of the methods to enhance the strength, ductility and toughness of the composites. Stir casting or friction stir processing technique was used to fabricate the metal matrix composite. For technology seekers it is very difficult to select appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 104 publications
0
34
0
Order By: Relevance
“…Alternative materials can be composites with a metal matrix reinforced with ceramic particles or fibres, the so-called cermets (metal matrix composite-MMC) [18][19][20]. These materials mainly feature a relatively low density (3.95 g/cm 3 for aluminium oxide, approximately 2.7 g/cm 3 for aluminium) and good mechanical properties, such as impact strength, tensile strength, yield strength or elongation [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative materials can be composites with a metal matrix reinforced with ceramic particles or fibres, the so-called cermets (metal matrix composite-MMC) [18][19][20]. These materials mainly feature a relatively low density (3.95 g/cm 3 for aluminium oxide, approximately 2.7 g/cm 3 for aluminium) and good mechanical properties, such as impact strength, tensile strength, yield strength or elongation [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that addition of Al2O3 results refined grain size in the composite. From previous reported review [14], it was found that B4C [15], SiC [16][17], and eggshell [18] was reinforced to aluminium alloy to form the composite.…”
Section: Introductionmentioning
confidence: 99%
“…The reinforced particle works as a grain nucleating site inside the solidifying specimen which obstruct the grain growth of the aluminum alloy. Thus, a consistent decrease in grain size with increased reinforcement of uniformly distributed reinforced particles was observed [5]. Secondly, FSP technique leads to intense plastic deformation that neutralizes the pinning effect.…”
Section: Introductionmentioning
confidence: 66%
“…Friction stir processing is newly emerged technique developed through FSW to develop surface composites. FSP technique is unable to fabricate bulk composites [5]. In FSP, non-consumable rotating tool is stirred above the specimen.…”
Section: Introductionmentioning
confidence: 99%